METHODS OF MODERN LABORATORY DIAGNOSIS OF BRUCELLOSIS - Djabbarova N.R.; Kudratova Z.E.; Xoliqulova B.; Egamqulova Y. (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Successful control of brucellosis can only be achieved through the mobilization of scientific resources, practical healthcare, and veterinary services, as brucellosis is a zoonotic infection to which all species of domestic and wild animals are susceptible. In recent years, there has been a steady increase in human cases of brucellosis, especially in areas with developed livestock farming.